Assessment of Percutaneous Laparoscopic Ultrasonography-Guided Core Needle Biopsy for the Advanced Diagnosis of Unresectable Pancreatic Cancer - Maemura, Kosei; Shinchi, Hiroyuki; Mataki, Yuko; Kurahara, Hiroshi; Iino, Satoshi; Sakoda, Masahiko; Ueno, Shinichi; Takao, Sonshin; Natsugoe, Shoji (JOP. Journal of the Pancreas, 2015)
Context Before the initiation of cytotoxic therapy for locally unresectable pancreatic cancer, staging laparoscopy is an important diagnostic method for both the detection of occult small lesions and the extraction of a tumor sample for advanced pathological examination using core needle biopsy (CNB) under laparoscopic ultrasonography (LUS) guidance. Objective This study aimed to evaluate the safety and usefulness of LUS-guided CNB in pancreatic cancer. Methods Consecutive patients with locally unresectable pancreatic cancer who underwent staging laparoscopy were retrospectively analyzed. LUS-guided CNB was performed percutaneously under a laparoscopic view. The clinical results of the LUS-guided CNB group and the non-LUS-guided CNB group were compared. Results Forty-eight patients who underwent staging laparoscopy by LUS-guided CNB or endoscopic ultrasound-guided fine needle aspiration were identified. LUS-guided CNB was performed in 25 patients. The mean tumor size in the LUS-guided CNB group was significantly larger than that in the non-LUS-guided CNB group. No significant difference was observed between the two groups in operating time or bleeding volume. The rates of malignancy diagnosis and histological classification subtyping were significantly higher in the LUS-guided CNB group. Histologically differentiated adenocarcinoma was identified in 15 patients using samples acquired by LUS-guided CNB. There was no uncontrollable bleeding or other complications, and a significant difference in the occurrence of peritoneal dissemination after laparoscopic examination was observed between the two groups. Conclusion LUS-guided CNB enables the safe acquisition of sufficient tissue volumes for certain pathological analyses required to determine treatment strategies for locally unresectable advanced pancreatic cancer. Image: Laparoscopic ultrasonography-guided core needle biopsy.